Influence of the processing methods on the properties of poly(lactic acid)/halloysite nanocomposites - De Silva, R. T. (John Wiley and Sons Inc., 2016)
The influence of processing methods on the thermo-mechanical properties of poly (lactic acid) (PLA) nanocomposites were investigated by preparing nanocomposites reinforced by halloysite nanotubes (HNTs) (from 0 to 10 [w/w%]) using solution casting (SC) and melt compounding (MC) methods. Statistical analysis revealed that the processing methods have a significant influence on the tensile properties, where nanocomposites prepared by MC have higher tensile properties compared to those by SC. Experimental results illustrated higher tensile strength and a drop in ductility under the higher strain rate as compared to the low strain rate for PLA/HNTs nanocomposites. At lower concentrations micrographs revealed that, HNTs dispersion was better for SC films as compared to MC, but more prominent HNTs aggregation at higher loadings. MC nanocomposites exhibited a high crystallinity as compared to SC, due to the recrystallization and nucleation effects. The thermal stability and activation energy increased with addition of HNTs, regardless of the processing methods.